Bear Skins and Macaroni: On Social Life of Things in a Siberian State Collective, and On the Performativity of Gift and Commodity Distinctions - Николай Владимирович Ссорин-Чайков (Journal of Economic Sociology, 2012)
This article explores a multiplicity of meanings of exchange and multiplicity of relations that are established through exchange. The article is based on long-term fieldwork in the north of the Krasnoyarsk region in Siberia, in which it was observed how a single item that was changing hands between the same people acquired different meanings. This exchange was understood as trade as well as gift at its different moments. The article approaches this interplay of meanings from the point of view of Michel Callon’s theory of performativity of economy. Callon’s focus is on performative relationship between market economy and economic knowledge. In the article, this focus is complemented with the idea of performativity of distinction between gifts and commodities. It is argued that in a situation in which meanings of exchange are exchanged in addition to material objects, it is this relationship between market and non-market exchange that it performative in Post-Soviet as well as in Soviet and older imperial power/knowledge relations. This argument is important for the anthropological gift theory, in which these distinctions are understood as descriptive, rather than performative. In conclusion, there is a discussion about opportunities of constructive dialog between economic sociology and anthropology on “single case study” methodology.